KEMATIAN MENURUT KAUM SUFI - Murtiningsih, Murtiningsih (Fakultas Ushuluddin dan Pemikiran Islam Universitas Islam Negeri Raden Fatah Palembang, 2015)
Death in Sufism is not a physical death. A Man can be told death if no longer does not he have a sensitivity of his surrounding. Eyes stare but they do not see, ears widely open but they do not hear, and noses can not smell. A man who has inability of the senses is the dead man. Allah has said in Koran An-Naml (27:80) . The dead man in the actual life has the dead soul. The dead soul is marked by the greaving when he leaves the religious command and without regretting when he makes the sins,